Implementing a care bundle approach reduces ventilator-associated pneumonia and delays ventilator-associated tracheobronchitis in children: differences according to endotracheal or tracheostomy devices. (November 2016) - Peña-López, Yolanda; Pujol, Montserrat; Campins, Magda; González-Antelo, Alicia; Rodrigo, Jose Ángel; Balcells, Joan; Rello, Jordi
Highlights: The impact of a care bundle on ventilator-associated pneumonia and ventilator-associated tracheobronchitis was different. Tracheostomy was the strongest risk factor associated with ventilator respiratory infections. The bundle was more effective in children with a tracheostomy than in those with an endotracheal tube. Summary: Objective: To reduce ventilator-associated infections (VARI) and improve outcomes for children. Methods: This prospective interventional cohort study was conducted in a paediatric intensive care unit (PICU) over three periods: pre-intervention, early post-intervention, and late post-intervention. These children were on mechanical ventilation (MV) for ≥48 h. Results: Overall, 312 children (11.9% of whom underwent tracheostomy) and 6187 ventilator-days were assessed. There was a significant reduction in ventilator-associated pneumonia (VAP) among tracheostomized patients (8.16, 3.27, and 0.65 per 1000 tracheostomy ventilation-days before the intervention, after the general bundle implementation, and after the tracheostomy intervention, respectively). The median time from onset of MV to diagnosis of ventilator-associated tracheobronchitis (VAT) increased from 5.5 to 48 days in the late post-intervention period ( p = 0.004), and was associated with a significant increase in median 28-day ventilator-free days and PICU-free days. Tracheostomy (odds ratio 7.44) and prolonged MV (odds ratio 2.75) were independent variables significantly associated with VARI. A trend towards a reduction in PICU mortality was observed, from 28.4% to 16.6% (relative risk 0.58). Conclusions: The implementation of a care bundle to prevent VARI in children had a different impact on VAP and VAT, diminishing VAP rates and delaying VAT onset, resulting in reduced healthcare resource use. Tracheostomized children were at increased risk of VARI, but preventive measures had a greater impact on them.